Analisis Minat Peternak terhadap Usaha Ternak Sapi Potong di Kecamatan Senyerang Kabupaten Tanjung Jabung Barat: Analysis of Breeders' Interest in Beef Cattle Farming in Senyerang District, West TanjungJabung Regency - ikhfa, ikhfa; Fatati, Fatati; Indra, Indra Sulaksana (BPFP Universitas Bengkulu, 2025)
Beef cattle farming is a crucial sector that substantially influences increasing rural household income.In Senyerang District, Tanjung Jabung Barat Regency, this potential has not been fully optimized.Several obstacles still persist, including limited capital access, feed availability, government support,land resources, and prevailing sociocultural conditions within the community. Therefore, it isnecessary to assess the extent of farmers’ interest in managing beef cattle farming. This study aims todescribe the level of farmers’ interest in beef cattle farming by analyzing six key aspects: economicvalue, capital, feed, land, sociocultural factors, and the role of government. The research was carriedout in April 2025 using a survey method with a descriptive quantitative approach. Data were collectedthrough questionnaires based on a Likert scale (1–3) and analyzed descriptively. A total of 52respondents were selected through purposive sampling, with the criterion of having receivedgovernment cattle assistance between 2010 and 2025. The study results indicate that the farmers’level of interest is categorized as high. Economic value, ease of feed acquisition, and land availabilitywere the most positively perceived factors. The long-established tradition of livestock rearing in thecommunity also contributes to the sustainability of this activity. However, some farmers still facechallenges related to capital. In conclusion, farmers in Senyerang District show a strong interest indeveloping beef cattle farming. These findings are expected to serve as a reference for relevantstakeholders in identifying regional potential and supporting sustainable livestock development.